Performance Improvement Through Talent Management, Career Development and Education in Mantri of PT Bank Rakyat Indonesia (BRI) Tbk Teluk Betung Branch - Fadlika Fadlika; Yudhinanto Cahyo Nugroho; Maria Septijantini Alie; Hasbullah Hasbullah; Eka Travilta Oktaria; Desi Derina Yusda (SAFE-Network, 2026)
This study investigates the influence of talent management, career development, and education on the performance of